Fungal kinases and transcription factors regulating brain infection in Cryptococcus neoformans - Kyung-Tae Lee (Nature Portfolio, 2020)
Cryptococcus neoformans causes fatal fungal meningoencephalitis. Here, the authors identify fungal kinases and transcription factors involved in blood-brain barrier crossing and brain infection in mice.